INTERNET BANKING SERVICE QUALITY IN INDONESIA AND ITS IMPACT ON E-CUSTOMER SATISFACTION AND E-CUSTOMER LOYALTY - Yohanes Ferry Cahaya; Indra Siswanti (Management Research Studies Journal, 2020)
This study proposes a model of the effect of internet banking service quality on e customer satisfaction and e customer satisfaction on e customer loyalty in the banking industry in Indonesia. Based on the technology acceptance model, this study aims to expand the model to better understand why consumers are willing or hesitant to adopt internet banking as a means of financial transactions. The researcher proposes a framework that integrates the factors that affect service quality, customer satisfaction, and customer loyalty. Some important implications are also discussed and the proposed model will form the basis of empirical studies.